The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1002/marc.1996.030171101
|View full text |Cite
|
Sign up to set email alerts
|

Propene polymerization catalyzed over MCM‐41 and VPI‐5‐supported Et(ind)2ZrCl2 catalysts

Abstract: Et(ind)zZrClz (C2H,(indenyl)zZrC12) confined inside regular pores of molecular sieves MCM-41 and VPIJ were prepared and used to polymerize propene with high activity. Stereoregularity, melting point and molecular weight of polypropene obtained were increased and the polymerization behavior was quite different from that prepared with homogeneous Et(ind)zZrC12. The small, regular and cylindrical pores of MCM-4 1 and VPI-5 suppress the formation of inactive binuclear complexes between metallocene and metallocene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Therefore, binding these metallocene catalysts onto inorganic supports as supported metallocene catalysts can overcome those drawbacks. Many inorganic supports such as SiO 2 , Al 2 O 3 , and MgCl 2 have been investigated [3][4][5][6][7][8][9]. It was reported that silica is perhaps the most attractive support so far.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, binding these metallocene catalysts onto inorganic supports as supported metallocene catalysts can overcome those drawbacks. Many inorganic supports such as SiO 2 , Al 2 O 3 , and MgCl 2 have been investigated [3][4][5][6][7][8][9]. It was reported that silica is perhaps the most attractive support so far.…”
Section: Introductionmentioning
confidence: 99%
“…Since the MCM-41 mesoporous silica (with a hexagonal arrangement of the pores with 2-5 nm diameter) was invented at the beginning of the 1990's [15][16][17], applications of mesoporous molecular sieves in controlled polymerization have attracted much attention [18,19]. In contrast to zeolites these materials have the ability to encapsulate relatively large molecules.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that many inorganic supports such as SiO 2 , Al 2 O 3 and MgCl 2 have been extensively studied. It was found that different supports could alter the catalytic behaviors during reaction as well [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%